2020
DOI: 10.1002/star.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biological Activities of Polysaccharides from Dandelion (Taraxacum officinale) Leaves

Abstract: A dandelion leaf polysaccharide (DLP) with a sugar content of 46.53 ± 2.22% is isolated using ultrasonic‐assisted enzymatic extraction. The DLP contains two polysaccharide fractions with respective molecular weights (Mw) of 1900 and 22 800 g mol−1. Gas chromatography analysis reveals a composition of rhamnose, arabinose, mannose, galactose, and glucose. DLP displays excellent water holding and oil holding capacities, along with a moderate emulsifying activity and stability. Following simulated digestion in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(42 reference statements)
0
0
1
Order By: Relevance
“…As shown in Figure 1 A, DLP120 showed a narrowly dispersed symmetrical peak on HPLC. The Mw relative to dextran of DLP120 measured by HPLC was 1.64 × 10 6 Da (based on the calibration curve y = −0.3434x + 9.3478, R 2 = 0.9914), which differs significantly from previous reports about small-molecule polysaccharides [ 30 , 31 ]. As shown in Figure 1 B, UV full-wavelength scanning confirmed that the DLP120 contained seldom nucleic acids or proteins.…”
Section: Resultscontrasting
confidence: 82%
“…As shown in Figure 1 A, DLP120 showed a narrowly dispersed symmetrical peak on HPLC. The Mw relative to dextran of DLP120 measured by HPLC was 1.64 × 10 6 Da (based on the calibration curve y = −0.3434x + 9.3478, R 2 = 0.9914), which differs significantly from previous reports about small-molecule polysaccharides [ 30 , 31 ]. As shown in Figure 1 B, UV full-wavelength scanning confirmed that the DLP120 contained seldom nucleic acids or proteins.…”
Section: Resultscontrasting
confidence: 82%